Education the surest preventive of crime, and the best safeguard of life, property, and social order - Haughton, James (Dublin Statistical Society, 1856)
Our national system in Ireland has been productive of great good. I would extend its advantages by increasing its funds, and by constantly widening its sphere of influence. No limit in these respects should be put to its operations. My own conviction is, that in order to make the system more truly national ? that is, to bring within its influence the entire population ? the education in our national schools should be exclusively secular and industrial in its character. Religious teaching should be conducted by parents and guardians, and by the clergy in whom they have confidence. The adoption of this principle would, as it seems to me, be the surest means of supplying a truly religious education also; as all parties would thereby be stimulated to exhibit, by the effects of their zealous labours, the excellent results of their various teachings. Manual labour for boys, and instruction in domestic economy for girls, seem to me essential for the promotion of virtue and happiness, and are therefore necessary elements of education suited for the prevention of crime, and the protection of life, property, and social order.
Read March 17th, 1856
Keywords: Education; Crime; 314.15